2019
DOI: 10.1051/0004-6361/201834457
|View full text |Cite
|
Sign up to set email alerts
|

The Herschel Dwarf Galaxy Survey

Abstract: The sensitive infrared telescopes, Spitzer and Herschel, have been used to target low-metallicity star-forming galaxies, allowing us to investigate the properties of their interstellar medium (ISM) in unprecedented detail. Interpretation of the observations in physical terms relies on careful modeling of those properties. We have employed a multiphase approach to model the ISM phases (H II region and photodissociation region) with the spectral synthesis code Cloudy. Our goal is to characterize the physical con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
191
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(216 citation statements)
references
References 110 publications
(114 reference statements)
24
191
0
1
Order By: Relevance
“…Distribution of the γ Low−zZ (left panel) and q PAH_Low−zZ (right panel) dust parameters from Draine & Li's models for the Low-zZ galaxy sample. The γ Low−zZ distribution peaks at 0.75 ± 0.07 and most of the q PAH = 0.47 which is the lowest value in Draine & Li's models.γ Low−zZ is assumed to be valid for the Hi-z LBG sample and q PAH_Low−zZ is fully consistent with our assumed q PAH_Hi−z Cormier et al 2019…”
supporting
confidence: 70%
“…Distribution of the γ Low−zZ (left panel) and q PAH_Low−zZ (right panel) dust parameters from Draine & Li's models for the Low-zZ galaxy sample. The γ Low−zZ distribution peaks at 0.75 ± 0.07 and most of the q PAH = 0.47 which is the lowest value in Draine & Li's models.γ Low−zZ is assumed to be valid for the Hi-z LBG sample and q PAH_Low−zZ is fully consistent with our assumed q PAH_Hi−z Cormier et al 2019…”
supporting
confidence: 70%
“…Theoretical and observed [C ii]/[N ii] 122 µm ratios are used to calculate the PDR gas fraction for the Galactic sample (Appendix E); a median of ∼ 60% of the [C ii] emission originates from the PDR gas component, broadly consistent with other estimates (Oberst et al 2011;Bernard-Salas et al 2012). Despite the large scatter for both Galactic and Magellanic samples, these fractions are also consistent with an increased contribution from the ionised gas component for higher metallicity environments (e.g., Cormier et al 2019, and references therein).…”
Section: [N Ii] Emissionsupporting
confidence: 62%
“…The advantage of the 145 µm line is that it is not affected by extinction and self-absorption. Cormier et al (2019) also showed that adding X-ray dominated regions to their cloudy models leads to a slight increase by a factor 1.2 in the [OI] 145 µm/63 µm luminosity ratio (their Fig. 8).…”
Section: Agn Contributionsmentioning
confidence: 85%
“…7) do not find such a trend in the local luminious infrared galaxies from GOALS. The only galaxies that show clearly higher [OIII] 88 µm / [OI] 63 µm ratios are dwarf galaxies, which has been interpreted as indicating the presence of low density channels allowing the hard UV photons to reach the outer parts of galaxies (Cormier et al 2015(Cormier et al , 2019. As a result, these low metallicity galaxies are likely to be filled with relatively low density (below n e − crit ([OIII] 88 µm)≃500 cm −3 ) gas rather than PDRs.…”
Section: Contributions Of Pdr and Hii Regionsmentioning
confidence: 99%